CD73+ Mesenchymal Stem Cells Ameliorate Myocardial Infarction by Promoting Angiogenesis - Li, Qiong; Hou, Huifang; Li, Meng; Yu, Xia; Zuo, Hongbo; Gao, Jianhui; Zhang, Min; Li, Zongjin; Guo, Zhikun (Frontiers in Cell and Developmental Biology, 2021)
With multipotent differentiation potential and paracrine capacity, mesenchymal stem cells (MSCs) have been widely applied in clinical practice for the treatment of ischemic heart disease. MSCs are a heterogeneous population and the specific population of MSCs may exhibit a selective ability for tissue repair. The aim of this study was to utilize the CD73+ subgroup of adipose derived MSCs (AD-MSCs) for the therapy of myocardial infarction (MI). In this study, AD-MSCs were isolated from adipose tissues surrounding the epididymis of rats and CD73+ AD-MSCs were sorted using flow cytometry. Overexpression and inhibition of CD73 gene of AD-MSCs using lentiviral vectors. To investigate the therapeutic effects of CD73+ AD-MSCs, 1.2×106 CD73+ AD-MSCs were transplanted into rat model of MI, and CD73- AD-MSCs, normal AD-MSCs transplantation served as control. Our results revealed that CD73+ AD-MSCs were more effective in the promotion function of cardiac recovery by promoting angiogenesis in a rat model of MI compared to mixed AD-MSCs and CD73- AD-MSCs. Moreover, the expression of CD73 promoted the secretion of VEGF, SDF-1α, and HGF factors in AD-MSCs. CD73+ AD-MSCs displayed significantly different transcription profiles compared to CD73-AD-MSCs, in particular, VEGF pathways. In conclusion, CD73+ AD-MSCs were the dominant subgroup, and the presence of the surface marker CD73 can be used as an MSCs cell quality control for the treatment of myocardial injury by promoting angiogenesis.